Keberhasilan Tatalaksana Infeksi Virus Hepatitis C di Rumah Sakit Umum Daerah dr. Zainoel Abidin Banda Aceh - dr. Azzaki Abubakar, Sp.PD-KGEH; dr. Andrie Gunawan, SpPD; Julia Sari (Journal of Medical Science, 2022)
Hepatitis C is a world health problem with a high mortality rate. The Indonesian Ministry of Health has been controlling hepatitis C infection since 2017 using Direct Acting Antiviral (DAA) drugs which have lower side effects and a higher cure rate. This study aims to determine incidence, patient demographic data, and liver fibrosis scores on the successful treatment of hepatitis C infection at RSUD dr. Zainoel Abidin Hospital. Inclusion criteria in this retrospective cohort design was patients with positive anti hepatitis C virus (Anti-HCV). Treatment was carried out when the viral load was detected by giving Sofosbuvir 400 mg per day and Daclatasvir 60 mg per day for 12 weeks, then patient returns to be examined to assess the successful therapy. Thirty eight out of 5002 patients (0.76%) showed positive Anti-HCV, most patients aged over 60 years (39.47%), was dominated by male (55.26%), and most of them are located in Banda Aceh (47 ,36 %). Thirty out of 38 positive anti-HCV patients (78.95%) had HCV RNA, but 15 patients (50%) were not eligible for treatment. Seven out of 15 patients (46.7%) completed DAA treatment. All HCV RNA were undetectable, improved AST values ​​and decreased aspartate aminotransferase-platelet ratio index (APRI) scores which showed improvement in liver fibrosis, after completing therapy. Hepatitis C patients who adhere to treatment and management of hepatitis C will get good results marked by improvement in liver fibrosis and undetectable HCV RNA.